Antiproliferative effects of Vanilla planifolia leaf extract against breast cancer MCF-7 cells - Kaliappan, Vijaybabu; Kumaravelu, Punnagai (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Breast cancer is the most common cancer disease among females in India and worldwide. This needs a critical research for finding the drugs to treat breast cancer with less side effects. The aim of the present study is to reveal the anti-proliferative effects of vanilla extract against MCF-7 cells. Methods: To reveal anti proliferative effects of vanilla leaf extract, MTT assay, cell cycle analysis and DNA fragmentation assay was performed as per standard protocols. Results: MTT assay showed decrease in cell viability with increase of dose of extract and revealed IC50 value at 31.2µg/ml. DNA fragmentation was seen in extract treated cells. Conclusions: The results of the present study confirm the antiproliferative property of vanilla leaf extract in MCF-7 cells. This study results conclude vanilla leaf extract as an effective plant source medicament for treating breast cancer.